Anaerobic digestion of organic waste: Recovery of value-added and inhibitory compounds from liquid fraction of digestate. (August 2021) - Lü, Fan; Wang, Zhijie; Zhang, Hua; Shao, Liming; He, Pinjing
Graphical abstract: Highlights: The production and recovery of valuable products in AD are reviewed. Closed-loop application of the recovered products in AD is proposed. More long-term and pilot-scale separation studies are needed in field application. Future opportunities lie in achievement of industrial stable in-situ extraction. Abstract: Anaerobic digestion, as an eco-friendly waste treatment technology, is facing the problem of low stability and low product value. Harvesting value-added products beyond methane and removing the inhibitory compounds will unleash new vitality of anaerobic digestion, which need to be achieved by selective separation of certain compounds. Various methods are reviewed in this study for separating valuable products (volatile fatty acids, medium-chain carboxylic acids, lactic acid) and inhibitory substance (ammonia) from the liquid fraction of digestate, including their performance, applicability, corresponding limitations and roadmaps for improvement. In-situ extraction that allows simultaneous production and extraction is seen as promising approach which carries good potential to overcome the barriers for continuous production. The prospects and challenges of the future development are further analyzed based on in-situ extraction and economics.